Usability of a digital mindfulness training program for smoking cessation: A mixed-method single-center pilot study protocol (HowToMind) - Anastasia Demina; Agnès Soudry-Faure; Benjamin Petit; Nicolas Meunier-Beillard; Benoit Trojak (PLoS ONE, 2025)
Background Tobacco use is one of the leading causes of preventable disease and death worldwide. Despite the availability of evidence-based pharmacological treatments, only a small number of individuals with tobacco use disorder achieve long-term abstinence after smoking cessation. This highlights the need to enhance existing interventions. In this protocol, we describe our single-center mixed-method trial, HowToMind, conducted in Dijon, France. This trial aims to investigate the usability and acceptability of a digital mindfulness-based intervention designed to complement standard smoking cessation treatment to potentiate its effects. Methods We will include 60 adults seeking treatment for tobacco use disorder, as defined by DSM-5 criteria, who wish to quit smoking and own a smartphone. All participants will receive a combination of transdermal and oral nicotine replacement therapy and will be introduced to an eHealth app that provides a digital equivalent of an 8-week mindfulness training program. The acceptability of the initial version of our app will be assessed based on usage frequency, and usability will be evaluated using the Mobile App Rating Scale (French version). A participatory approach will be employed through focus groups conducted at the end of the 8 weeks of app use, aimed at co-constructing the final version of the app based on participant feedback. Discussion Our pilot mixed-method trial seeks to explore the usability and acceptability of our app, making necessary adjustments to its content and functionality based on participant feedback before its implementation in a large randomized controlled trial assessing the app’s potential to enhance the effects of standard treatment. Trial registration ClinicalTrials.gov, NCT06500117.